Meeting the challenge of inpatriation – a cultural perspective - Jessica Karch (Hochschule für Angewandte Wissenschaften Hamburg, 2018)
Inpatriation becomes increasingly important in today’s staffing policies. However, in order to be able to exploit its full benefits, potential challenges must first be diminished. The most significant challenge this thesis has identified are cross-cultural adjustment problems. Within the area of cross-cultural adjustment, six aspects have been explored to cause difficulties: 1) a high organizational cultural distance, 2) role and acceptance problems, 3) a high national cultural distance, 4) family adjustment issues, 5) unrealistic expectations and 6) language barriers. Hence, two approaches are proposed, which meet all six challenges. These approaches focus especially on acceptance and corporate culture difficulties as these two aspects are considered most challenging for inpatriates. The first approach proposes that on the short-term a cross-cultural training should be developed, which includes corporate culture in its content and is adapted to the variety of backgrounds of inpatriates. On the long-term, the value of diversity should be integrated into the overall corporate culture and the HR strategy adapted to the needs of inpatriates. Both approaches together can then ensure the exploitation of the benefits of inpatriation in the short as well as in the long-term.
Keywords: inpatriation; inpatriate manager; cross-cultural adjustment; diversity management; cultural d